Capturing, induced spawning, and first feeding of wild-caught Pseudopimelodus mangurus, an endangered catfish species - Arashiro, Dilberto Ribeiro [UNESP]; Yasui, George Shigueki [UNESP]; Calado, Leonardo Luiz; Nascimento, Nivaldo Ferreira do [UNESP]; Alves do Santos, Silvio Carlos; Shiguemoto, Gustavo Fonseca [UNESP]; Monzani, Paulo Sergio; Senhorini, Jose Augusto [UNESP] (Univ Catolica De Valparaiso, 2020)
This study aimed to describe a procedure for sampling, reproduction, and first feeding of the Neotropical catfish Pseudopimelodus mangurus, an endangered fish species. Wild adult P. mangurus specimens were collected in the Mogi Guassu River and subsequently induced to spawn in laboratory conditions. After hand-stripping, the females, the average weight of the oocytes was 143 +/- 1.6 g, with a fecundity of 718 +/- 49.8 oocytes g(-1). The diameter of the oocytes non-hydrated was 1,226.3 +/- 47.7 mu m to 1,761.2 +/- 26.4 mu m after hydration. The fertilization rates were 98.00 +/- 0.63%, and the hatching rate was 68.94 +/- 11.83%. The first feeding was made three days post-hatching with six different treatments, in which the best results arose with sequential feeding with Artemia nauplii, Astyanax altiparanae and Prochilodus lineatus larvae. This condition resulted in a final length of 2,012.7 +/- 44.8 mu m by the 10th day of the experiment, higher survival (65 +/- 0.9%) and lower cannibalism rate (14 +/- 0.3%). The data obtained in this study is important for the establishment of reproductive biotechniques, mass production of P. mangurus, and future establishment of ex-situ GenBank.
Keywords: Pseudopimelodus mangurus; catfish; conservation; GenBank; larvae; reproduction